HUBUNGAN TOLERANSI DAN KOEKSISTENSI DALAM BERAGAMA PERSPEKTIF TAFSIR AL-QUR’AN - Izzatul Ulumiyah Ulufi; M. Mukhid Mashuri; Ahmad Zainuddin; Miftara Ainul Mufid (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
This study examines the relationship between religious tolerance and coexistence from the perspective of the Qur'an as the normative foundation of multicultural society. The phenomenon of misunderstanding about the limits of tolerance, the mixing of religious practices, and the erroneous interpretation of pluralism demonstrates the importance of studies based on Islamic teachings. This study uses library research with the tahlili interpretation method for QS. Al-Baqarah (2): 256, QS. Al-Kafirun (109): 1–6, QS. Yunus (10): 40–41, and QS. Al-Hujurat (49): 13. The analysis is carried out through linguistic studies, verse contexts, and interpretations by classical and contemporary commentators. The results of this study indicate that the Qur'an emphasizes the importance of tolerance as an attitude of respecting differences in beliefs without coercion in religion, while also emphasizing the boundaries of faith. On the other hand, coexistence is understood as a social implementation of tolerance, namely living side by side peacefully, fairly, and respectfully amidst diversity. Therefore, tolerance and coexistence are two interrelated concepts in building social harmony without eliminating religious identity.